Unraveling the Magnesium Connection: The Cincinnati PPG's Pioneering Work on Mineral Metabolism in Diabetes and Pregnancy - Mimouni, Francis B.; Khoury, Jane C.; Ehrlich, Shelley; Rosen, Barak; Sheffer-Mimouni, Galit; Miodovnik, Menachem (American Journal of Perinatology, 2024)
This study aimed to review the Cincinnati PPG's contribution to the understanding and treatment of neonatal hypocalcemia (NHC) in infants of diabetic mothers. This study is a retrospective review of the NIH-funded Program Project Grant (PPG) works related to mineral metabolism in type 1 diabetic pregnant women. The PPG investigators first described the epidemiology and the additional risk factors for NHC, namely prematurity and neonatal asphyxia, but also recognized the independent effect of maternal diabetes mellitus. They explored the link between NHC and maternal/neonatal hypomagnesemia. They finally conducted a randomized control trial of prevention of NHC by early administration of magnesium sulfate soon after birth to prevent NHC. The PPG in its various phases has allowed to reveal the important role that magnesium plays in the regulation of mineral metabolism in pregnancy and in particular the pregnancy complicated by pregestational diabetes.
Keywords: magnesium deficiency; neonatal hypocalcemia; neonatal hypomagnesemia; type 1 diabetes mellitus